REVITALIZATION OF THE VALUE OF MADURA'S HOSPITALITY THROUGH THE ESTABLISHMENT OF TRADITIONAL VILLAGES ON GILIYANG ISLAND - Shaleh, Akhmad Muwafik (Jurnal Al-Ijtimaiyyah, 2025)
This research aims to revitalize the value of Madurese hospitality through the establishment of a traditional village on Giliyang Island, Sumenep. The value of hospitality, which is a characteristic of the Madurese people, has great potential to be integrated in the development of culture-based tourism. With a communication ethnographic approach, this study seeks to read the opportunities for the formation of customary villages, understand the values of Madura hospitality, and formulate revitalization strategies that are relevant to local social and cultural conditions. Giliyang Island, with its distinctive natural wealth, such as high oxygen levels and alluring panoramas, is a strategic location for the development of traditional villages. Research has found that the value of community hospitality, such as mutual cooperation and respect for guests, can be a significant cultural tourism attraction. The proposed traditional villages not only preserve traditions but also provide economic benefits through the improvement of the tourism sector and the creative economy. The results of the study show that the local community strongly supports the establishment of this customary village. Around 75% of respondents stated the importance of preserving customs to maintain cultural identity. The establishment of customary villages is also supported by the local government which is committed to providing infrastructure and training for the community. The proposed strategy involves the active involvement of local communities, strengthening cultural education for the younger generation, and promoting hospitality values as a tourist attraction.